Regulatory VCAN polymorphism is associated with shoulder pain and disability in breast cancer survivors - Trevor S. Mafu; Alison V. September; Delva Shamley (Human Genomics, 2021)
Abstract Background and purpose Shoulder morbidity following breast cancer treatment is multifactorial. Despite several treatment- and patient-related factors being implicated, unexplained inter-individual variability exists in the development of such morbidity. Given the paucity of relavant genetic studies, we investigate the role of polymorphisms in candidate proteoglycan genes. Patients and methods We conducted a cross-sectional study on 254 South African breast cancer survivors, to evaluate associations between shoulder pain/disability and ten single nucleotide polymorphisms (SNPs) within four proteoglycan genes: ACAN (rs1126823 G>A, rs1516797 G>T, rs2882676 A>C); BGN (rs1042103 G>A, rs743641 A>T, rs743642 G>T); DCN rs516115 C>T; and VCAN (rs11726 A>G, rs2287926 G>A, rs309559). Participants were grouped into no–low and moderate–high shoulder pain/disability based on total pain/disability scores: < 30 and ≥ 30, respectively using the Shoulder Pain and Disability Index (SPADI). Results The GG genotype of VCAN rs11726 was independently associated with an increased risk of being in the moderate-to-high shoulder pain (P = 0.005, OR = 2.326, 95% CI = 1.259–4.348) or disability (P = 0.011, OR = 2.439, 95% CI = 1.235–4.762) categories, after adjusting for participants’ age. In addition, the T-T-G inferred allele combination of BGN (rs74364–rs743642)–VCAN rs11726 was associated with an increased risk of being in the moderate-to-high shoulder disability category (0 = 0.002, OR = 2.347, 95% CI = 1.215–4.534). Conclusion Our study is first to report that VCAN rs11726, independently or interacting with BGN polymorphisms, is associated with shoulder pain or disability in breast cancer survivors. Whereas our findings suggest an involvement of proteoglycans in the etiology of shoulder pain/disability, further studies are recommended.